The Valproate Checklist in a female psychiatric intensive care unit. (1st April 2018) - Howe, Andrew; Nasreen, Raihana; Brammer, Faith; Varma, Seema; Sethi, Faisil
Valproate has been increasingly prescribed for acute and maintenance treatment in bipolar affective disorder (BPAD). In females with BPAD who are prescribed valproate, risks of teratogenicity are of particular concern. A checklist produced by the Medicines & Healthcare Products Regulatory Agency (MHRA) attempts to ensure that the risks of teratogenicity are discussed with patients. We surveyed the completion of this checklist in a female psychiatric intensive care unit (PICU) over a period of six months. We also considered the components of the checklist in relation to its aims. Only 6 out of 15 patients had a fully completed checklist on leaving the PICU, suggesting that this is not the ideal clinical environment to ensure its full completion. Patient's lack of capacity was the main reason given for it not being fully completed. Improvements are suggested to the checklist content to ensure access to contraception is offered to patients along with folic acid prescription.